Klinične raziskave v fitoterapiji - Kočevar Glavač, Nina (Farmacevtski vestnik, 2013)
In modern medicine and pharmacy, clinical trials represent an important tool for evaluation of safety and efficacy of drugs, including herbal medicines. Specific features of designing and conducting clinical trials in phytotherapy originate in complex chemical composition of medicinal plants or bioactive compounds. The article represents the basics of clinical trials, specific features of clinical trials in phytotherapy, and cases of clinical trials assessing the effectiveness of Echinacea drugs.
Keywords: ameriški slamnik; Echinacea sp.; fitoterapija; klinične raziskave